Gendered Moral Agency and Qur'anic Hermeneutics of Sexuality: A Ma'na-cum-Maghza Reading on the Story of Yusuf and Zulaykha - Siti Robikah; Izza Royyani; Muhammad K. Ridwan (QiST: Journal of Quran and Tafseer Studies, 2026)
This article investigates the gendered ethics of sexuality in Q.S. Yūsuf [12]:23–24 through Sahiron Syamsuddin's ma'na-cum-maghza hermeneutical framework, which integrates textual meaning with evolving ethical significance. Contemporary social discourses frequently construct sexuality as a burden borne by women, casting them as primary sexual objects and assigning responsibility for sexual misconduct to their bodies and behavior. Traditional interpretations of the Yūsuf–Zulaykhā episode have often reinforced this imbalance by foregrounding female desire while minimizing male sexual agency. Through a linguistic, contextual, and intratextual analysis (ma'na), followed by an exploration of historical, contemporary, and ideal significances (maghza), this study argues that the Qur'anic narrative actually affirms a more equitable ethical vision. The text acknowledges both Yūsuf and Zulaykhā as sexual subjects possessing desire and moral agency, while distinguishing them based on the ethical management of that desire rather than on gender. The findings demonstrate that: (1) sexual inclination is a universal human condition rooted in fiṭrah; (2) moral accountability applies equally to men and women; and (3) wrongdoing arises not from sexuality itself, but from its coercive or unjust enactment. Thus, the narrative offers a Qur'anic foundation for gender-equitable sexual ethics, challenging patriarchal interpretations that stigmatize female desire and absolve male responsibility.